Multi‐synergistic chemotherapeutic drug assemblies to activate colorectal cancer immunotherapy by modulating the multilevel immunosuppressive characteristics - Rongrong Zheng; Chuyu Huang; Hangyu Zhou; Lixin Zhao; Qiuyuan Li; Guangmiao Chen; Linping Zhao; Shiying Li (Aggregate)
Abstract The life‐threatening colorectal cancer exhibits multilevel immunosuppressive characteristics, including low immunogenicity, abnormal cellular metabolism, and acidic immunosuppressive microenvironment. In this work, multi‐synergistic chemotherapeutic drug assemblies are fabricated to activate colorectal cancer immunotherapy by modulating the multilevel immunosuppressive characteristics. Without any drug excipients, the glycolysis inhibitor of lonidamine (LON), indoleamine 2,3‐dioxygenase 1 (IDO‐1) inhibitor of NLG919 (NLG), and the photosensitizer of chlorine e6 could self‐assemble into drug assemblies (LNC) with uniform nano‐size distribution and increased drug stability. Moreover, LNC could also promote cellular uptake and enhance drug penetration to enable efficient drug co‐delivery. Especially, the photodynamic therapy (PDT) of LNC could disrupt tumor cells to release tumor‐associated antigens, thus efficiently suppressing primary tumor growth and improving tumor immunogenicity. Meanwhile, LNC could also reduce the activity of IDO‐1 and attenuate the glycolysis metabolism, thereby reversing the multilevel immunosuppressive characteristics to promote T cell activation. Benefiting from the multi‐synergistic effects, LNC efficiently eradicates the primary tumor growth and also activates systemic antitumor immunity for metastatic tumor inhibition. Such a simple formulation but a multi‐synergistic strategy may accelerate the development of translational nanomedicine for colorectal cancer immunotherapy by using small molecular drug combinations.